Poverty and ethnicity among black South Africans - Carlos Gradin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper investigates inequalities across the major black ethnic groups in South Africa, accounting for 80 per cent of the country's population. We demonstrate that there is an important ethnic gap in the poverty levels of the Xhosa and the Zulu with respect to the Sotho/Tswana. We also show that these gaps are largely associated with the former groups having an accumulation of disadvantages in location, demographic structure, education, and labour market outcomes. The analysis of the evolution that occurred after the end of apartheid shows that the gap might have increased, especially in the case of the Zulu.
Keywords: D31; I32; J15; O15; 330; poverty; ethnicity; South Africa; Xhosa; Zulu; Sotho/Tswana